One-Step Electrochemical Fabrication of Lithium-Intercalated Pencil Graphite Electrode (PGE) for the Differential Pulse Voltammetric (DPV) Determination of l-Tyrosine - Serbest, Zeynep; Gorduk, Ozge; Sahin, Yucel (TAYLOR & FRANCIS INC, 2023)
Tyrosine (l-Tyr), which is found in basic foods, is a nonessential amino acid and a metabolite of phenylalanine, has many roles in human metabolism, and is important in maintaining nutritional balance. In this study, an electrochemical method has been presented to determine low levels of l-Tyr using an electrochemically treated pencil graphite electrode (EPGE) via overoxidation of graphite surface and intercalation of Li+ ions into graphite by cyclic voltammetry in the potential range between -0.3 and 2.0 V. Characterization studies of the EPGEs were carried out using scanning electron microscopy, energy-dispersive X-ray spectroscopy, electrochemical impedance spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy, and cyclic voltammetry. The determination of l-Tyr was performed by differential pulse voltammetry, and the investigation of electrochemical properties of l-Tyr was conducted by cyclic voltammetry. The results showed that the EPGE presents high electrocatalytic performance and has a low detection limit (0.12 mu M) for determining l-Tyr with a wide linear range from 1.0 to 500 mu M. The selectivity of prepared EPGE was investigated in the presence of organic species. The determination of l-Try was performed in yoghurt and milk samples and good results were obtained with recoveries between 95.7% and 103.1%. Stability and repeatability studies further demonstrate the applicability of the sensor.
Keywords: Differential pulse voltammetry (DPV); electrochemically treated pencil graphite electrode (EPGE); electrochemical treatment; l-tyrosine; GLASSY-CARBON ELECTRODE; GRAPHENE OXIDE; ASCORBIC-ACID; L-TRYPTOPHAN; IMPEDANCE SPECTROSCOPY; MASS-SPECTROMETRY; URIC-ACID; PHENYLALANINE; NANOPARTICLES; DOPAMINE; Chemistry